Outcome of epilepsy surgery in focal cortical dysplasia. Issue 2 (1st February 2003) - Kral, T; Clusmann, H; Blümcke, I; Fimmers, R; Ostertun, B; Kurthen, M; Schramm, J
Abstract : Objective: To describe the outcome of surgery in patients with drug resistant epilepsy and a histopathological diagnosis of focal cortical dysplasia. Methods and subjects: Analysis of histories and presurgical and follow up data was carried out in 53 patients with a histological diagnosis of focal cortical dysplasia. Their mean age was 24.0 years (range 5 to 46), and they included 14 children and adolescents. Mean age at seizure onset was 12.4 years (0.4 to 36) and mean seizure duration was 11.6 years (1 to 45). Results: The presurgical detection rate of focal cortical dysplasia with magnetic resonance imaging (MRI) was 96%. There were 24 temporal and 29 extratemporal resections; additional multiple subpial transections were done in 12 cases to prevent spread of seizure discharges. There was a 6% rate of complications with permanent neurological deficit, but no deaths. All resected specimens were classified by neuropathological criteria as focal cortical dysplasia. Balloon cells were seen in most cases of extratemporal focal cortical dysplasia. After a mean follow up of 50 months, 38 patients (72%) were seizure-free, two (4%) had less than two seizures a year, nine (17%) had a reduction of seizure frequency of more than 75%, and four (8%) had no improvement. Seizure outcome was similar after temporal and extratemporal surgery. The patients in need of multilobar surgery had the poorest outcome. Conclusions: Circumscribed lesionectomy of focal dysplastic lesions provides seizure relief in patients with chronic drug resistant temporal and extratemporal epilepsy. There was a trend for the best seizure outcome to be in patients with early presurgical evaluation and early surgery, and in whom lesions were identified on the preoperative MRI studies.